Non-absorbable versus absorbable sutures for anterior colporrhaphy: study protocol for a randomised controlled trial in South Korea. Issue 6 (16th June 2020) - Jeon, Myung Jae; Suh, Dong Hoon; Kim, Chul Hong; Cho, Hyun-Hee; Shin, Jung-Ho; Lee, Sa Ra; Jung, Yong Wook; Kim, Soo Rim; Kong, Mi Kyung
Abstract : Introduction: The anterior vaginal wall is the segment most commonly affected by prolapse. Traditionally, anterior vaginal wall prolapse is repaired via anterior colporrhaphy, which is known to have a high recurrence rate. Several factors might affect the outcome of anterior colporrhaphy, and the use of absorbable sutures might also be associated with the high recurrence rate because the sutures might not be able to retain adequate strength until the plicated pubocervical fascia remodels and regains maximum tensile strength. Nonetheless, no comparative data exist about the relative efficacy and safety of anterior colporrhaphy using non-absorbable versus absorbable sutures. The objective of this study is to compare the surgical outcomes of anterior colporrhaphy using non-absorbable sutures with those of anterior colporrhaphy using absorbable sutures. Methods and analysis: This is a randomised, multicentre, superiority trial. Anterior colporrhaphy will be performed in a traditional manner with midline plication of the fibromuscular layer using either non-absorbable or absorbable sutures. The primary outcome is composite surgical success 1 year after surgery defined as the absence of all of the following: (1) anterior vaginal descent beyond the hymen, (2) the presence of vaginal bulge symptoms and (3) retreatment for recurrent anterior vaginal wall prolapse with either surgery or pessary. The secondary outcomes include the individual components of the composite primary end point, anatomical outcomes, condition-specific quality of life and adverse events related to anterior colporrhaphy. The planned number of participants is 192. Ethics and dissemination: This study was approved by the Institutional Review Board of Seoul National University Hospital (H-1810-037-977). The results of the study will be published in peer-reviewed journals, and the findings will be presented at scientific meetings. Trial registration number: NCT03736811